Automation of Software Defined Network (SDN) Configuration Management Based on Proxmox with Ansible - Marzuki, Khairan; Husain, Husain; Apriliana, Zikriati (International Journal of Electronics and Communications Systems, 2024)
Automation of software-defined networking (SDN) in Proxmox VE 8.1 enhances virtual network management by improving efficiency, scalability, and the speed of network configuration changes. This study aims to automate SDN configuration management in Proxmox VE using Ansible and evaluate its performance. The research follows the Network Development Life Cycle (NDLC) method, consisting of six stages: Analysis, Design, Simulation Prototyping, Implementation, Monitoring, and Management. Automation was implemented successfully using an Ansible playbook to manage creating and deleting zones, VNets, subnets, IP gateways, and DHCP ranges. The automated process was tested over three trials, with creation times of 23, 20, and 21 seconds and deletion times of 20, 19, and 20 seconds, respectively. By contrast, the manual process required 6 minutes 6 seconds for creation and 2 minutes 37 seconds for deletion. These results demonstrate that automation using Ansible significantly reduces configuration time, offering a more efficient and reliable approach than manual methods. The findings highlight the potential of Ansible to streamline SDN management in Proxmox VE, saving time, energy, and resources while ensuring scalability and consistency in virtualized network environments.